Persistent electrocardiographic ST segment elevation from previous myocarditis - Efrén Martinez-Quintana; Fayna Rodriguez-Gonzalez; Paula Junquera-Rionda (Wolters Kluwer Medknow Publications, 2013)
Various conditions may present with an electrocardiographic pattern of ST segment elevation simulating myocardial infarction. We present an asymptomatic 16-year-old male patient, whose ECG showed persistent anterolateral ST segment elevation and magnetic resonance imaging showed wall motion abnormalities from previous myocarditis but no evidence of inflammation.